NEOFORMATION OF SOMATIC EMBRYOS-LIKE STRUCTURES FROM CORK-OAK (QUERCUS-SUBER L) TISSUE-CULTURES - ELMAATAOUI, M.; ESPAGNAC, H. (COMPTES RENDUS DE L ACADEMIE DES SCIENCES SERIE III-SCIENCES DE LA VIE-LIFE SCIENCES, 1987)
Embryoid-like formations were induced on cork-oak (Quercus suber L.) calluses grown in vitro on Murashige and Skoog's médium, supplemented with IBA and BAP. Thèse formations rapidly differenciated an apical meristem, flanked with two cotylédons, and a radicular meristem on the opposite end. In most cases embryoids' development stopped there, as if meristems became dormant immediately after their organization. But under certain culture conditions these somatic embryos can produce a great number of secondary embryoids. This multiplication capacity seems to be maintained over generations
The following values have no corresponding Zotero field: pub-location: 127 AVE DE LA REPUBLIQUE, 92120 MONTROUGE, FRANCE publisher: JOHN LIBBEY EUROTEXT LTD